Delayed breastfeeding initiation increases risk of neonatal mortality. - Edmond, K; Zandoh, C; Quigley, M; Amenga-Etego, S; Owusu-Agyei, S; Kirkwood, B (2006)
BACKGROUND: Breastfeeding promotion is a key child survival strategy. Although there is an extensive scientific basis for its impact on postneonatal mortality, evidence is sparse for its impact on neonatal mortality. OBJECTIVES: We sought to assess the contribution of the timing of initiation of breastfeeding to any impact. METHODS: This study took advantage of the 4-weekly surveillance system from a large ongoing maternal vitamin A supplementation trial in rural Ghana involving all women of childbearing age and their infants. It was designed to evaluate whether timing of initiation of breastfeeding and type (exclusive, predominant, or partial) are associated with risk of neonatal mortality. The analysis is based on 10,947 breastfed singleton infants born between July 2003 and June 2004 who survived to day 2 and whose mothers were visited in the neonatal period. RESULTS: Breastfeeding was initiated within the first day of birth in 71% of infants and by the end of day 3 in all but 1.3% of them; 70% were exclusively breastfed during the neonatal period. The risk of neonatal death was fourfold higher in children given milk-based fluids or solids in addition to breast milk. There was a marked dose response of increasing risk of neonatal mortality with increasing delay in initiation of breastfeeding from 1 hour to day 7; overall late initiation (after day 1) was associated with a 2.4-fold increase in risk. The size of this effect was similar when the model was refitted excluding infants at high risk of death (unwell on the day of birth, congenital abnormalities, premature, unwell at the time of interview) or when deaths during the first week (days 2-7) were excluded. CONCLUSIONS: Promotion of early initiation of breastfeeding has the potential to make a major contribution to the achievement of the child survival millennium development goal; 16% of neonatal deaths could be saved if all infants were breastfed from day 1 and 22% if breastfeeding started within the first hour. Breastfeeding-promotion programs should emphasize early initiation as well as exclusive breastfeeding. This has particular relevance for sub-Saharan Africa, where neonatal and infant mortality rates are high but most women already exclusively or predominantly breastfeed their infants.